Optical Biopsy Instrument Design and Parameter Extraction from Hyperspectral Time-Resolved Fluorescence Data - Badr, Fares (My University, 2019)
Complete resection is correlated to better patient outcome in aggressive cancers such as glioblastoma. Optical biopsy refers to a family of techniques utilizing optical properties of living targets to make diagnoses where a biopsy would conventionally be used. Such a technology can potentially guide neurosurgeons in removing glioblastomas. Diffuse reflectance (DR) and Time-resolved fluorescence (TRF) have previously been investigated for their ability to measure biomarkers indicative of cancer. One of the difficulties faced in using TRF as a diagnostic tool is that multiple endogenous fluorophores will simultaneously contribute to the signal. This makes it difficult to attribute fluorescence lifetimes or spectral changes to one type of molecule in the tissue. This thesis focuses on the challenge of separating the components in a TRF measurement and their fractional contributions. A DR-TRF instrument was designed and built and characterized using fluorescent dyes. An orthonormal basis deconvolution method combined with a Fourier-domain method were tested for their ability to unmix fluorescent components in a hyperspectral TRF measurement. This method was tested on dye mixtures and retrieved fluorescence lifetimes of 4.6±0.4 ns and 2.7±0.2 ns in a mixture of Fluorescein and Coumarin-6 at concentrations of 5 μM each. It was also tested on an ex-vivo brain tissue where the fluorescence was approximated as a sum of 2 components.
Keywords: Optical Biopsy; Fluorescence Lifetime; Diffuse Reflectance; Phasor Analysis